MINERALOGICAL AND GEOCHEMICAL CHARACTERIZATION OF ZEOLITES IN ALBANIAN OPHIOLITIC PLAGIOGRANITES - Goga Beqiraj, E.; Muller, F.; Beqiraj, A. (Bulletin of the Geological Society of Greece, 2016)
The plagiogranites, that represent the uppermost part of the plutonic complex of the Albanian ophiolites, are intensively altered. They crop out in the north - eastern sectors of the Albanian ophiolitic complex presenting intrusive contacts with volcanic and gabbroic rocks. The zeolite, that is a typically secondary mineral, has filled thin veins and/or small vesicles of the rock. From the XRD, EMPA and microscopic analyses it is concluded that this zeolite belongs to the laumontite - leonhardite (LAU) series.